Determination of Sex Using Hyoid Bones in Forensic Identification: a Systematic Review - istiana firqah abid; Qurotul Ainayah (Universitas Udayana, 2025)
The hyoid bone, a single bone structure in the human neck, has significant potential in forensic identification, particularly for sex determination. This study aims to evaluate the effectiveness of anthropometric measurements and morphological analysis of the hyoid bone across different populations. Using the PRISMA protocol and databases such as Publish or Perish, Science Direct, and Google Scholar, 130 initial studies were identified, with 10 relevant articles selected for detailed analysis. The results reveal significant differences in the dimensions of the hyoid bone, such as length and width, between males and females in various populations. Morphometric analysis demonstrated a 73% accuracy rate in sex identification based on specific characteristics. Other studies utilizing CT-scan techniques reported high accuracy in sex differentiation, with an area under the ROC curve reaching 81.8%. This research also highlights variations in hyoid bone dimensions influenced by population characteristics, analytical methods, and measurement techniques. For instance, the average size of the hyoid bone in males tends to be larger than in females, with statistically significant differences across studies. These findings emphasize the importance of considering population-specific factors in forensic data interpretation. The study concludes that the hyoid bone is a reliable tool for sex determination, especially when methods involve morphometric measurements and CT-scan techniques. Collaboration among forensic experts, radiologists, and anthropologists is recommended to enhance the accuracy and validity of identification outcomes. A systematic approach to using the hyoid bone has the potential to strengthen modern forensic practices with robust scientific foundations.